Self-assembled nanorods in YBCO matrix - a computational study of their effects on critical current anisotropy - Elmeri Rivasto; Mukarram Zaman Khan; Mika Malmivirta; Hannes Rijckaert; Moe Moe Aye; Teemu Hynninen; Hannu Huhtinen; Isabel Van Driessche; Petriina Paturi (NATURE PUBLISHING GROUP, 2025)
In order to understand how the doping with self-assembled nanorods of different sizes and concentrations as well as applied magnetic fields affect the critical current anisotropy in YBa2Cu3O7−x (YBCO) thin films close to YBCO c-axis, we present an extensive and systematic computational study done by molecular dynamics simulation. The simulations are also used to understand experimentally measured Jc(θ) curves for BaHfO3, BaZrO3 and BaSnO3 doped YBCO thin films with the help of nanorod parameters obtained from transmission electron microscopy measurements. Our simulations reveal that the relation between applied and matching field plays a crucial role in the formation of Jc(θ)-peak around YBCO c-axis (c-peak) due to vortex-vortex interactions. We also find how different concentrations of different size nanorods effect the shape of the c-peak and explain how different features, such as double c-peak structures, arise. In addition to this, we have quantitatively explained that, even in an ideal superconductor, the overdoping of nanorods results in decrease of the critical current. Our results can be widely used to understand and predict the critical current anisotropy of YBCO thin films to improve and develop new pinscapes for various transport applications.